Role of Brf1 interaction with ERα, and significance of its overexpression, in human breast cancer. Issue 12 (27th October 2017) - Fang, Zeng; Yi, Yunfeng; Shi, Ganggang; Li, Songqi; Chen, Songlin; Lin, Ying; Li, Zhi; He, Zhimin; Li, Wen; Zhong, Shuping
Abstract : TFIIB‐related factor 1 (Brf1) modulates the transcription of RNA Pol III genes (polymerase‐dependent genes). Upregulation of Pol III genes enhances tRNA and 5S RNA production and increases the translational capacity of cells to promote cell transformation and tumor development. However, the significance of Brf1 overexpression in human breast cancer (HBC) remains to be investigated. Here, we investigate whether Brf1 expression is increased in the samples of HBC, and we explore its molecular mechanism and the significance of Brf1 expression in HBC. Two hundred and eighteen samples of HBC were collected to determine Brf1 expression by cytological and molecular biological approaches. We utilized colocalization, coimmunoprecipitation, and chromatin immunoprecipitation methods to explore the interaction of Brf1 with estrogen receptor alpha (ERα). We determined how Brf1 and ERα modulate Pol III genes. The results indicated that Brf1 is overexpressed in most cases of HBC, which is associated with an ER‐positive status. The survival period of the cases with high Brf1 expression is significantly longer than those with low levels of Brf1 after hormone treatment. ERα mediates Brf1 expression. Brf1 and ERα are colocalized in the nucleus. These results indicate an interaction between Brf1 and ERα, which synergistically regulates the transcription of Pol III genes. Inhibition of ERα by its siRNA or tamoxifen reduces cellular levels of Brf1 and Pol III gene expression and decreases the rate of colony formation of breast cancer cells. Together, these studies demonstrate that Brf1 is a good biomarker for the diagnosis and prognosis of HBC. This interaction of Brf1 with ERα and Brf1 itself are potential therapeutic targets for this disease. Abstract : Drug‐resistant and triple‐negative cases remain a major therapeutic challenge of breast cancer. TFIIB‐related factor 1 (Brf1) is overexpressed in most cases of this disease. Estrogen receptor positive (ER+) patients with high Brf1 expression display longer survival and good prognosis after hormone treatment. ERα and Brf1 synergistically modulate Pol III gene transcription. Tamoxifen represses expression of Brf1, which is a potential target for breast cancer therapy.